A concept for the mobilization of a critical mass on the basis of Walter Benjamin's philosophy of history - Rehm, Rafael (Momentum Quarterly, 2017)
The article aims to depict the epistemological program of Walter Benjamin in terms of his concept of a knowledge of history. The intention of this depiction is to elaborate a method that makes an alternative reading of historic processes possible. Besides this, the intention is to question the difference between Walter Benjamin’s conception and Hegel’s conception of knowledge of history. In this formulation of a question the differences between the dialectic of Hegel and Benjamin’s conception of it will be discussed. The alternative reading of Walter Benjamin which makes a materialistic interpretation of the present time possible and helps to mobilize a critical mass will be questioned and discussed in the following article.
Keywords: philosophy of history; Walter Benjamin; dialectic; critical mass